THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING AND THE INCIDENCE OF STUNTING IN TODDLERS - Dita Hasni; Natasya Syifa Anugrah; Zilhadi Al Asri; Sri Nani Jelmila (Nusantara Hasana Journal, 2023)
Motivation/Background. Stunting represents a prevalent health issue, particularly in lower to middle-income countries, including Indonesia. Occurring predominantly among infants, stunting is influenced by various factors such as genetics and nutritional status, primarily derived from direct dietary intake like breastfeeding. Additionally, socioeconomic factors, including household income, economic status, and food security, also contribute to stunting in young children. The adverse effects of stunting manifest in compromised growth and intellectual development, potentially impeding productivity, elevating the incidence of low birth weight, and increasing the risk of degenerative diseases. These consequences may subsequently heighten the risk of future poverty. This study aims to explore the relationship between exclusive breastfeeding and the incidence of stunting in infants. Method: The research adopts a (narrative/systematic) review methodology, guided by the PRISMA 2020 framework. Data was gathered through searches on Google Scholar and PubMed, focusing on publications from 2019 to 2023. The search keywords included "Relationship between Exclusive Breastfeeding and Stunting," "Exclusive Breastfeeding," and "Stunting." Out of 100 results from Google Scholar and 756 from PubMed, five studies were selected for inclusion in this review.Results: The review indicates that the incidence of stunting is significantly associated with the lack of exclusive breastfeeding during the first six months of life. Conclusions: There is a significant correlation between exclusive breastfeeding and the incidence of stunting in infants, underlining the importance of promoting and supporting exclusive breastfeeding to mitigate the risk of stunting and its long-term consequences